PERANCANGAN GEDUNG KESENIAN TARI DAN PEWAYANGAN KOTA BEKASI MELALUI PENDEKATAN ARSITEKTUR EKOLOGI - Nadia Sabrina; Mieke Choandi (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
As times goes by, the culture adopted became more eroded, this causes us to forget the importance of culture, spirituality, ethics and morals. Especially in the city of Bekasi which is a peri-urban city which is located between the city and the village. Traditional dance and puppetry are well known as local culture, however, it is now on a verge of an extinction. it relates to forgotten culture of the City of Bekasi resulting in the loss of the identity of the City of Bekasi. The development of a function as a fulfillment of human needs must consider the surrounding natural environment and the reciprocal relationship between humans and their environment. Therefore, the use of ecological architectural principles needs to be applied. The purpose of the project is to preserve the arts of dance and puppet culture in the City of Bekasi. The design method uses the principles of ecological architecture. Source ZEB concept by utilizing sunlight as a building energy source and applying a system of Grey-water recycling and rainwater collection. The mass is in the form of an arch so that the building is more dynamic. The mass is made of terraces for airing and natural lighting can enter so that the utilization of renewable natural resources can be maximized. Keywords:  Art hall; Ecological architecture; Ecology AbstrakPerkembangan zaman terus terjadi sehingga semakin tergerus budaya yang dianut, hal ini mengakibatkan kita lupa akan pentingnya budaya, spiritual, etika dan moral. Khususnya pada Kota Bekasi yang merupakan kota peri-urban dimana terletak antara pusat kota dan desa. Tari dan pewayangan Kota Bekasi cukup dikenal sebagai budaya setempat namun, terus mengalami kepunahan. Hal ini berkaitan langsung dengan mulai terlupakannya budaya Kota Bekasi mengakibatkan hilangnya identitas Kota Bekasi. Pembangunan suatu fungsi sebagai pemenuhan kebutuhan manusia haruslah mempertimbangkan lingkungan alam sekitar dan hubungan timbal balik antar manusia dan lingkungannya. Maka dari itu, Penggunaan prinsip arsitektur ekologi perlu diterapkan dalam bangunan. Tujuan proyek sebagai upaya pelestarian kesenian tari dan pewayangan Budaya Kota Bekasi. Metode perancangan menggunakan prinsip arsitektur ekologi. Konsep Source ZEB dengan memanfaatkan sinar matahari sebagai sumber energi bangunan dan menerapkan sistem Grey-water recycling dan penampungan air hujan. Massa berbentuk melengkung agar bangunan lebih dinamis. Massa di buat berundak untuk pengudaraan dan pencahayaan alami dapat masuk sehingga pemanfaatan sumber daya alam terbarui dapat maksimal.